Design and Development of a Unity 2D Math Educational Game for Elementary Students’ Arithmetic Skills - Moh Shiddiq Windiarto; Ahmed Mahdi Jubair (CV. Laskar Karya, 2025)
Mathematics learning at the elementary school level often faces challenges due to students’ low motivation and difficulties in understanding abstract arithmetic concepts. Conventional teaching methods that rely heavily on textbooks and lectures tend to make students less engaged in learning activities. Therefore, an interactive and enjoyable learning medium is needed to support students in understanding basic arithmetic operations. This study aims to develop a Unity 2D–based math educational game as an alternative learning medium to improve elementary students’ arithmetic skills and learning motivation. The research employed a research and development approach using the Extreme Programming model, which consists of planning, design, coding, and testing stages. Data were collected through observation, interviews, and documentation to identify user needs and system requirements. The developed game integrates arithmetic materials such as addition, subtraction, multiplication, and division into interactive gameplay supported by visual elements, scoring systems, levels, and immediate feedback mechanisms. System testing was conducted using black-box testing to evaluate functionality and usability testing to measure user satisfaction. The results indicate that the developed educational game operates properly and provides an engaging learning experience for students. The implementation of gamification elements successfully increases students’ motivation and supports their understanding of arithmetic concepts. This study concludes that the Unity 2D–based math educational game can serve as an effective interactive learning medium for improving arithmetic skills and supporting technology-based learning in elementary education.